Intraperitoneal analgesia to reduce pain after laparoscopic hysterectomy - Badawy, Amira Mohammed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Laparoscopic hysterectomy is now an established operation, as it is less invasive and carries much less post-operative pain compared to open hysterectomy. However, post-laparoscopy analgesia is still a challenge. Intraperitoneal (IP) instillation of local anaesthetics has been shown to minimize postoperative pain after laparoscopic surgeries. This study was conducted to evaluate the efficacy of IP instillation of dilute analgesia prior the end of laparoscopic hysterectomy to reduce postoperative pain. The primary outcome was to assess postoperative pain scores. Secondary outcomes included assessment of postoperative analgesic requirements (type, amount, and timing), and frequency of nausea and vomiting. Methods: 20 cases were enrolled for laparoscopic hysterectomy and were divided randomly into two groups, Group A: 10 cases, where IP analgesia (Bupivacaine and Magnesium Sulphate) was instilled -under vision- prior removal of trocars, and Group B: 10 cases, where no IP analgesia was used. After surgery, Visual Analogue Score (VAS) was recorded at 6, 12, 24 hours and 7 days. Postoperative analgesic requirements (type, amount, and timing), and frequency of nausea and vomiting were also recorded. Results: The overall VAS during the first postoperative 24 hours was significantly lower in group A (P = 0.048, 0.049, and 0.003 at 6, 12, and 24 hours after surgery). Time to first of analgesia required (in hours) was longer (6.0±1.41 vs 3.20±1.48, P = 0.004) and total analgesic consumption (in mg) was lower (2.40±0.89 vs 3.30±0.67, P = 0.047) in group A compared to group B. The need for opioids was also significantly less in group A (3 cases vs 8 cases, P = 0.024). in group A, nausea and vomiting were less reported as well (P = 0.040). Conclusions: The instillation of local IP dilute analgesia is an effective and safe method for reducing pain after laparoscopic hysterectomy.